A draft phased assembly of the diploid Cascade hop (Humulus lupulus) genome. Issue 1 (18th February 2021) - Padgitt‐Cobb, Lillian K.; Kingan, Sarah B.; Wells, Jackson; Elser, Justin; Kronmiller, Brent; Moore, Daniel; Concepcion, Gregory; Peluso, Paul; Rank, David; Jaiswal, Pankaj; Henning, John; Hendrix, David A.
Abstract: Hop ( Humulus lupulus L. var Lupulus) is a diploid, dioecious plant with a history of cultivation spanning more than one thousand years. Hop cones are valued for their use in brewing and contain compounds of therapeutic interest including xanthohumol. Efforts to determine how biochemical pathways responsible for desirable traits are regulated have been challenged by the large (2.8 Gb), repetitive, and heterozygous genome of hop. We present a draft haplotype‐phased assembly of the Cascade cultivar genome. Our draft assembly and annotation of the Cascade genome is the most extensive representation of the hop genome to date. PacBio long‐read sequences from hop were assembled with FALCON and partially phased with FALCON‐Unzip. Comparative analysis of haplotype sequences provides insight into selective pressures that have driven evolution in hop. We discovered genes with greater sequence divergence enriched for stress‐response, growth, and flowering functions in the draft phased assembly. With improved resolution of long terminal retrotransposons (LTRs) due to long‐read sequencing, we found that hop is over 70% repetitive. We identified a homolog of cannabidiolic acid synthase (CBDAS) that is expressed in multiple tissues. The approaches we developed to analyze the draft phased assembly serve to deepen our understanding of the genomic landscape of hop and may have broader applicability to the study of other large, complex genomes. Core Ideas: We present an improved reference genome assembly of the hop that better characterizes the genome heterozygosity and gene and repeat content. We estimate that the repeat content of the hop genome is over 70%. Genes with high divergence between haplotypes are enriched for growth and defense functions. We found a homolog of cannabidiolic acid synthase that is expressed in multiple tissues. We developed broadly applicable approaches to analyze phased genome assemblies.